Population Approaches for Detecting Glucose Disorders. - Lee, Crystal; Colagiuri, S. (2016)
Globally, 382 million adults aged 20-79 years are estimated to have diabetes and 46% are unaware of their condition. Another 316 million adults are at increased risk of developing diabetes. Although there are suggestions that diabetes and related complications can be prevented through early detection, lifestyle intervention and/or treatment, universal screening for diabetes has not been adopted. There are, instead, recommendations for a multi-step screening approach, which include identifying people at risk of diabetes through non-invasive methods such as a risk assessment tool or presence of diabetes risk factors, followed by blood testing for the at risk group and diagnostic blood testing for those screened positive for diabetes. Diabetes screening initiatives have been studied in different medical, health and community settings and some have targeted high risk populations. Most of these screening initiatives, however, have common limitations such as low follow-up rate with primary care providers for those who screen positive, abnormal screening result not communicated to the at risk person's primary care provider, failure to provide appropriate follow-up for patients with abnormal screening results, time and cost as barriers for both screening providers and people invited for screening, and low acceptance of the oral glucose tolerance test.If these common limitations can be addressed, diabetes screening initiatives have the potential to detect undiagnosed diabetes in most populations.